Carbon Cantilever Beam Health Inspection Using a Polymer Fiber Bragg Grating Array - Theodosiou, Antreas; Komodromos, Michael; Kalli, Kyriacos (My University, 2018)
We demonstrate a quasi-distributed sensor for cantilever health inspection measurements using a fiber Bragg grating (FBG) array inscribed in a polymer optical fiber. The FBGs were characterized and calibrated for axial strain, temperature, and relative humidity prior to their mounting on a carbon cantilever beam, the tail rotor of a helicopter. By using the zero-crossing demodulation algorithm, we recovered the time-dependent, wavelength response from each Bragg grating sensor and the vibration response of the beam was extracted. We used the response of the beam to study how the addition of masses at different positions on the beam influences the vibrational behavior and mimics the location of 'damage' through the time-dependent results. We show that health inspection measurements are feasible with polymer-based fiber Bragg gratings, offering accurate and rapid detection of damage points on a structural beam.
Keywords: Femtosecond laser; Fibre Bragg gratings; Polymer fibre; Structural monitoring; Vibration measurements